Safety issues in the development of the experimental model for an innovative medical parallel robot used in brachytherapy. Issue 3 (1st February 2017) - Pisla, Doina; Galdau, Bogdan; Covaciu, Florin; Vaida, Calin; Popescu, Daniela; Plitea, Nicolae
Abstract : The paper presents a medical parallel robot (BR-1), designed for the minimally invasive, targeted, treatment of cancer through brachytherapy. The analysis of Jacobi matrices allows a complete study of the singularities while generating also a set of conditions which, implemented in the control system, enable the safe behaviour of the robot. Brachytherapy is an advanced form of cancer treatment involving the placement of small radioactive seeds directly inside the malignant tumour, allowing a very effective, local treatment of cancer. For this task an innovative parallel robotic system has been developed, having five degrees of freedom, constructed in two versions, BR-1R and BR-1T with a slight variation at the level of a passive joint. The two solutions revealed different accuracy distributions and by selecting the proper variant based on the tumour location, an increased universality degree for the BR-1 robot is obtained. The singularity-free workspace is determined using the assessment of singularities for both robot versions. The control system for both robot versions is simple, robust and intuitive allowing clinicians to have an accurate procedure, having real-time force monitoring during the needle insertion. The experimental data demonstrate that the robotic structure is a worthy candidate for robotic-assisted brachytherapy.